Small-scale maize farmers' willingness to pay for changing planting dates in the face of climate change : a case study of Makhuduthamaga Local Municipality, Limpopo Province - Tau, Lekobane Lebogang (My University, 2023)
The agricultural sector plays an important role in South Africa regardless of the small contribution of 1.88% it has to the GDP of the Country. Small-scale maize farmers’ decisions to adopt adaptation options in response to climate change and variability are influenced by socioeconomic, institutional, and environmental factors, indicating that decision patterns can be very specific to a given locality. The study aimed to analyse the determinants of small-scale maize farmers’ willingness to pay for changing planting dates in the face of climate change. This study had two main objectives, to identify and describe the socio-economic characteristics of small-scale maize farmers, and to determine factors influencing the small-scale maize farmer’s willingness to pay for changing planting dates in the face of climate change in Makhuduthamaga Local Municipality. The study used primary data with a sample size of 150 small-scale maize farmers. Descriptive statistics and the Probit Regression Model were employed when analysing data. The study employed purposive sampling in the data collection process and three villages were selected. Probability was proportional to sample size and was used to select the number of small-scale maize farmers for the sample frame of each village. About 58% of the sampled small-scale maize farmers were willing to pay for changing planting dates in the face of climate change, as opposed to 42% of those not willing to pay for changing planting dates. Empirical results from the analysis reported that age (10%), educational level (1%), level of income (1%), years of farming (10%), total output (1%), exposure to climate information services (5%), and use of indigenous forecast (1%) out of twelve explanatory variables were found to be significant. Based on the empirical findings of the study it is recommended that government officials together with other stakeholders such as NGOs and research institutions should invest in the education of small-scale maize farmers through knowledge systems such as (presentations, conferences, seminars, abet etc). Government policies and strategic investment plans that support improved small-scale maize farmers’ accessibility to climate information are also recommended.
Thesis (M.Sc. (Agricultural Economics)) -- University of Limpopo, 2023
Keywords: Small-scale maize farmers; Climate change; Planting dates; Willingness to pay; Climatic changes; Willingness to pay; Farmers -- South Africa; Farmers